2013
DOI: 10.4103/2152-7806.116926
|View full text |Cite
|
Sign up to set email alerts
|

Intraorbital arteriovenous fistula with thrombosed varix: Diagnosis and treatment without catheter angiography in a developing country

Abstract: Background:Pure intraorbital arteriovenous fistula (AVF) that do not connect to the cavernous sinus are quite rare. Presence of thrombosed varix in association with a spontaneous onset pure orbital AVF is even rarer.Case Description:We report an interesting case of a 50-year-old female with pure intraorbital AVF of spontaneous onset with thrombosed varicose superior ophthalmic vein (SOV). She presented with 18 months history of right eye proptosis, upper lid swelling, and conjunctival chemosis with recent onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…Mishra et al 7 also reported a case of pure intra orbital AVF with thrombosed varicose SOV, which was similar to ours. Their patient, on the other hand, had a lengthy history of proptosis, chemosis, and a recent onset of retro-orbital pain and reduced vision, spanning 18 months.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Mishra et al 7 also reported a case of pure intra orbital AVF with thrombosed varicose SOV, which was similar to ours. Their patient, on the other hand, had a lengthy history of proptosis, chemosis, and a recent onset of retro-orbital pain and reduced vision, spanning 18 months.…”
Section: Discussionsupporting
confidence: 89%
“…AVF, unlike AVMs, begins with a single contact between an artery and a vein but no nidus. 1 , 6 , 7 Intra-orbital AVFs are most usually caused by a physical lesion to the ethmoid artery, such as a fracture of the ethmoid bone and a rupture in the ocular venous system. 6 , 7 Fistulas can develop rapidly in non-traumatic situations due to artery degeneration caused by atherosclerosis, hypertension, or other vascular disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most cases are secondary to traumatic events, such as a fracture of the ethmoid bone, or spontaneous. The vast majority of cases have been described in cases after trauma; however, a few cases have been documented spontaneously in patients with a prior history of hypertension, atherosclerosis, and other vascular diseases [1]. Purely intra-orbital AVF are very rare, in fact, only about 26 cases have been reported in the literature [2].…”
Section: Discussionmentioning
confidence: 99%
“…Intra-orbital AVFs may be easily miss-diagnosed due to its rarity and common presentation. Symptoms usually involve proptosis, diplopia, ocular hypertension, and engorged episcleral vessels [1]. Vision loss and abnormal ocular movement are usually not present.…”
Section: Discussionmentioning
confidence: 99%